الأحكام القانونية للأجزاء المشتركة في الملكية العقارية الطابقية بموجب القانون رقم 55 لعام 2002م - شربا رشا; الفتال رشا فيصل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن ظاهرة انتشار الأبنية ذات الملكية العقارية الطابقية، والانتقال من حالة البناء الأفقي إلى حالة البناء العمودي، له من المزايا في مواجهة أزمة السكن التي تعاني منها سوريا، كما له من المساوئ التي تمثلت بتفكك الروابط بين المالكين بسبب الخلافات على صيانة وإدارة الأجزاء المشتركة مما أدى إلى عدم العناية الواجبة بمرافق المبنى المشترك فتعطل الكثير منها، وأصبحت مصالح المالكين أنفسهم مهددة. فالنظام القانوني الذي اتخذه المشرع في الملكية العقارية الطابقية يشمل البناء المكون من عدة طبقات أو شقق، وكل طبقة تتكون من أجزاء خاصة وأجزاء مشتركة، الأمر الذي أوجب علينا الإشارة إلى ماهية الأجزاء المشتركة، وخصائصها، والتكييف القانوني لها، بالإضافة إلى آليات تحديدها وتحديد نصيب الشاغل في الأجزاء المشتركة. The phenomenon of the spread of buildings with the ownership of the real estate floor, and the transition from the state of horizontal construction to the state of urban construction, it has advantages in the face of the housing crisis experienced by Syria, as well as the disadvantages of the disintegration of the links between owners because of differences on the maintenance and management of the common parts, Due to lack of due diligence on common building facilities, many of which have been disrupted, and the interests of the owners themselves have been threatened. The legal system adopted by the legislator in the ownership of the real estate floor includes the construction consisting of several layers or apartments, each layer consists of special parts and parts of the joint, which required us to indicate what the common parts and characteristics, and the legal adaptation to them, in addition to mechanisms to identify and share the concern In the shared parts.